YKL-40 Is Associated With Ultrasound-Determined Carotid Atherosclerotic Plaque Instability - Wang, Yu; Li, Bohong; Jiang, Yong; Zhang, Runhua; Meng, Xia; Zhao, Xingquan; Wang, Yongjun; Zhao, Xihai; Liu, Gaifen (Frontiers in Neurology, 2021)
Background and aims: YKL-40, an inflammatory biomarker, has been reported to be involved in the process and progression of atherosclerosis. Several studies have investigated the association between YKL-40 and plaque, and suggested YKL-40 might be a potential biomarker for plaque instability. The purpose of this study was to investigate the association between YKL-40 and carotid plaque instability. Methods: Based on a community-based study in Beijing from February 2014 to May 2016, 1132 participants with carotid plaques were enrolled in this study. Data on demographic, medical history were collected through face-to-face interview, and fasting blood samples were collected and stored. We use ultrasound to evaluate the presence of carotid plaque and its instability. The level of YKL-40 was measured by enzyme-linked immunosorbent assay (ELISA). Multivariate logistic regression analysis was performed to investigate the association between YKL-40 levels and carotid atherosclerotic plaque instability. Results: The mean age of the 1132 participants was 58.0 (52.0-64.0) years, and 560 (49.5%) were male. Unstable plaques were detected in 855 (75.53%) participants. YKL-40 level were classified into four groups according to its quartile: quartile 1: <25.47 ng/ml, quartile 2: 25.47-39.53 ng/ml, quartile 3: 39.53-70.55 ng/ml, quartile 4: ≥70.55 ng/ml. After adjusting for age, gender, smoking, alcohol drinking, medical history, triglycerides, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, homocysteine, and hs-CRP, the top quartiles of YKL-40 level were significantly associated with unstable plaque (quartile 3: OR 2.53, 95%CI 1.65-3.89; quartile 4: OR 1.98, 95%CI 1.27-3.11). Conclusion: This study demonstrates that YKL-40 is associated with carotid plaque instability. People with high YKL-40 have a higher risk of unstable carotid plaque, which may be an independent risk factor for carotid plaque instability.